DFT studies of Hg0 oxidation by gaseous advanced oxidation method: H2O2/Fe3O4 (1 1 1) and hydroxyl pre-adsorbed Fe3O4 (1 1 1) surface. (15th August 2017) - Zhou, Changsong; Wang, Ben; Song, Zijian; Ma, Chuan; Yu, Jie; Zhang, Zhiyue; Yang, Hongmin; Sun, Lushi
Graphical abstract: The optimized configurations of Hg on Fetet1 -terminal and Feoct2 -terminal OH/Fe3 O4 (1 1 1) surface. Highlights: The mechanism of H2 O2 decomposition and OH generation on Fe3 O4 (1 1 1) was studied. Hg 0 oxidation processes on hydroxyl pre-adsorbed surface were compared. The major reaction pathway of Hg oxidation product on Fe3 O4 (1 1 1) was discussed. Abstract: Elemental mercury oxidation mechanism by gaseous advanced oxidation method was studied using density functional theory on Fe3 O4 (1 1 1) surface containing H2 O2 molecule. Fetet1 - and Feoct2 -terminated Fe3 O4 (1 1 1) surfaces have been simultaneously considered both in H2 O2 decomposition and hydroxyl pre-adsorbed Fe3 O4 (1 1 1) interfaces. It is found that the Feoct2 -terminated surface was more favored for H2 O2 decomposition, and H2 O2 was easier to decompose and generate two hydroxyls than Fetet1 -terminated surface. Through the discussion of Fetet1 - and Feoct2 -terminal mechanisms, the Mulliken charge population, and the partial density of states, we found that OH had different reaction activity generated on different Fe-terminal. Hg strongly interacted with the free state OH mainly due to the highly reactive and strong electrophilic ability of OH radical. The oxidation of Hg formed stable oxidized mercury species on Fe-terminated surface and most of the lost electron transferred from Hg to unbonded hydroxyl during Hg oxidation. The result showed that the combination of Hg and hydroxyl was exothermic reaction, which was favorable to spontaneous processes of Hg oxidation. The OH–Hg–OH and Hg–OH intermediates had a lower desorption energy when they detached from the surface and was the major reaction pathway.